Calcium Absorption and Bioavailability of Isoflavones from Tempeh Compared to Milk Among Postmenopausal Malay Women - Haron, Hasnah (2009)
The main objective of this study was to determine the absorption of calcium from tempeh compared to milk and apparent bioavailability of isoflavone in urinary excretions of postmenopausal Malay women consuming tempeh. There were three phases in this study. In phase one, food analyses on tempeh showed every 100 g of fried tempeh contained 41.8 ± 5.1% moisture, 18.6 ± 1.2% crude protein, 18.8 ± 7.2% crude fat, 19.9 ± 3.4% total carbohydrate, 0.8 ± 0.2% total ash, 63.3 ± 2.7 mg Ca, 34.57 ± 11.07 mg daidzein (DA) and 30.50 ± 11.41 mg genestein (GE), based on wet weight. Deep frying tempeh in batter for 30 minutes decreased 45% of the total isoflavones in fried tempeh (113 ± 41 mg) compared to the raw one (205 ± 56 mg). Raw tempeh contained the highest total amount of DA (25.64 ± 5.65 mg) and GE (28.41 ± 9.15 mg) compared to other studied local soy products. In phase two, health screening was conducted to select healthy subjects for clinical trial in phase three. Ethical approval was obtained from the ethical committee of Universiti Kebangsaan Malaysia Medical Centre (UKMMC) prior to the study. A total of 125 postmenopausal Malay women screened from five locations in suburban of Kuala Lumpur and 42 of them met the inclusion criteria and were qualified to take part in the clinical trial. The mean age of the subjects was 59 ± 4 years and they were on average 10 ± 7 years postmenopausal. Average weight, height and body mass index (BMI) for these subjects were 63.7 ± 10.1 kg, 1.5 ± 0.1 m and 28.1 ± 4.2 kg/m2. Majority (46%) of the women was overweight while 31% were obese and two percent were underweight. Two-thirds of them have been taking medication for chronic diseases like hypertension (27%), diabetes mellitus (9%), heart disease (1%) and combination of the three chronic diseases (19%). Average values for fasting serum lipid for these subjects were 5.97 ± 1.23 mmol/L of total cholesterol (TC), 1.40 ± 0.33 mmol/L of high density lipoprotein cholesterol (HDLC), 3.84 ± 1.02 mmol/L of low density lipoprotein cholesterol (LDLC) and 1.77 ± 0.96 mmol/L of triglyceride (TG). About 74% of subjects were hypercholesterolemic and 58% were hypertriglyceridemic. Based on the calcaneal measurement, 37% of the subjects were osteopenic while 6% were osteoporotic. Based on the dietary history questionnaire, average calcium intake of the subjects was 505 ± 263 mg/d when. Their main source of calcium was obtained from vegetables (37%), dairy products (32%), meat and seafood (17%), cereal (7%), fruits (5%) and beverages (2%). Using the semi food frequency questionnaire (SFFQ) for soy products the average estimated isoflavone intake for these subjects was 25 ± 15 mg/d. The most frequently consumed soy products for this population was tempeh (25%), fujook (17.4%), homemade soy bean drink (11.2%), unfried tofu (10.3%), fried tofu (8.9%), tofufah (8.4%), soft tofu (7.4%), boxed soy bean drink (7.2%) and egg tofu (4.3%). In phase three, 21 healthy postmenopausal Malay women volunteered to take part in the clinical trial for calcium absorption and apparent bioavailability study. The study was carried out at the in patient clinical trial ward of UKMMC. Only 20 subjects completed the study since one subject was excluded for not completing the urine collection. The mean age of these subjects was 57 ± 3 years and they were on average 9 ± 5 years postmenopausal. Average weight, height and BMI for these subjects were 63 ± 11 kg, 1.5 ± 0.1 m and 27 ± 4 kg/m2. Majority (55%) of these women was overweight while 20% were obese. Measurement of bone mineral density (BMD) using dual energy absorptiometry (DXA), indicated that 50% of the subjects was osteopenic, 35% were normal and 15% were osteoporotic. Body weight was significantly correlated to the BMD of the total body (r = 0.457, p = 0.037) and neck (r = 0.507, p = 0.019). Based on 3-day food records, 20 postmenopausal Malay women have average low calcium intake of 426 ± 122 mg/d, and 30% of them have reported of not taking any milk. Their mean values for parathyroid hormone (PTH), serum 25-hydroxyvitamin D (25(OH)D), urinary deoxypyridinoline (DPD) and serum alkaline phosphatase (BAP) were : 59.5 ± 21.6 pg/ml, 11.1 ± 4.1 ng/ml, 11.1 ± 1.8 nmol/mmol and 37.1 ± 8.3 U/L, respectively. The majority (95%) subjects had serum 25(OH)D less than 20 ng/ml, which are indicative of vitamin D insufficiency. Correlation analysis showed a significant inverse association between serum 25(OH)D and BMI (r = - 0.388, p = 0.045,). About 30% of the subjects had secondary hyperparathyroidism with PTH concentrations exceed 65 pg/ml. Fractional calcium absorption from tempeh was compared to that observed from milk, using a dual stable isotope approach in a randomized cross-over design. Subjects consumed the same calcium load (130-150 mg Ca) from either milk or tempeh with a one-month washout period between each test meal. 42Ca (0.036 mg/kg) was administered intravenously to subjects prior to oral administration of 44Ca (0.272 mg/kg) in milk. All urine from subjects was collected for 24 h post-dosing in 8 h pools. Average percent calcium absorption from tempeh (36.9 ± 10.4%) was not significantly different (p>0.05) from that observed from milk (34.3 ± 8.4%). Estimated calcium balance (VBal) from taking tempeh (108 ± 63 mg/d) was significantly higher (p<0.05) compared to milk (71 ± 64 mg/d). Apparent bioavailability of isoflavones was determined from the urinary isoflavone excretions following ingestion of 240 g tempeh (160 mg isoflavones) and milk. Tempeh consumption for day one was carried out at the clinical trial ward and the same three-8h urine pool collected for calcium absorption study at the ward was used for isoflavone study. Tempeh consumption and 24 h urine collection for day two and three was carried out at subjects’ home. DA, GE, equol (EQ) and flavone (FLA) standards eluted at mean retention time of 16.8 ± 0.1, 20.6 ± 0.1, 21.1 ± 0.1, 25.4 ± 0.1 min, respectively. An average excretion of 3.51 ± 0.62 μmol/h DA and 2.79 ± 0.35 μmol/h GE were detected after consumption of milk. DA (47.06 ± 4.18 μmol/h), GE (33.27 ± 3.71 μmol/h) and EQ (24.35 ± 4.34 μmol/h) were detected in three-8 h urine pool, following tempeh consumption (Day 1). There was a significant correlation (r = 0.453, p = 0.045) between percent calcium absorption and total isoflavone excretion in 9-16 h urine pool. Urinary isoflavone excretions following ingestion of tempeh (Day 1) were significantly higher (p<0.05) compared to that of the milk. The average amount of total isoflavones consumed in three days of tempeh consumption was 154.83 ± 1.82 mg per day. Total isoflavones excreted in each day one, two and three of tempeh consumption were as follows: 104.68 ± 9.21, 32.64 ± 3.18 and 30.25 ± 3.99 μmol/day, respectively. The average isoflavone excreted from three days of tempeh consumption were 26.16 ± 2.64 μmol/h DA, 16.64 ± 1.98 μmol/h GE and 13.06 ± 1.79 μmol/h EQ. Almost all subjects excreted EQ following three days of tempeh consumption. There was only one subject (5%) that can be classified as equol producer based on ratio of equol produced to daidzein consumed >0.2. Isoflavone intake of the 20 subjects was estimated to be 26 ± 13 mg per day, ranging from 6 - 58 mg. Based on SFFQ for soy products, the frequently consumed local soy products were consisted of tempeh (19.6%), fujook (16.5%), firm tofu (13.4%), fried firm tofu (11.3%), tofufah (10.3%), homemade SB drink (10.3%), boxed SB drink (7.2%), soft tofu (6.2%) and egg tofu (5.2%) In conclusion, this sample of postmenopausal Malay women has low calcium intake that achieved only 40 - 50% of the Malaysian RNI. Low intake of calcium among these subjects may be due to their predominantly non-milk based diet where 30-40% of them do not take any milk. Calcium bioavailability from tempeh provided similar amounts of absorbed calcium to that obtained from a glass of milk. These findings indicated that tempeh may have the potential to contribute significantly to the calcium needs of these postmenopausal Malay women who were at risk of low bone mass and were insufficient of vitamin D. Increased incorporation of tempeh, the affordable and available plant sources of calcium and isoflavones may contribute significantly to the calcium needs of this high-risk population and also help to reduce the abnormal serum lipid levels in majority of these subjects.